A Review of Developments in the Fields of the Design of Smart Cutting Tools, Wear Monitoring, and Sensor Innovation. Issue 10 (2019) - Hopkins, C.; Hosseini, A.
Abstract: As advances in manufacturing technology grow, so does the need for better cutting tools and sensors to execute and monitor manufacturing processes, respectively. By integrating these concepts, the development of smart cutting tools was created. The purpose of this paper is to provide a review of several major fields regarding the development and applications of smart cutting tools. This review will detail works published in chronological order that made significant contributions and provided a platform to allow for further work to be done.